Some Forms of Systematic Development of Teachers' Professional Skills: Advanced Practices and Recommendations - Soliyev Ilhomjon Sobirjonovich; Kodirova Tabassum Alisher kizi (Zien Journals, 2023)
Based on the analysis of the requirements of the profession to the personality of a specialist, the concept of professionalism is introduced. Professionalism is a set of personal characteristics of a person necessary for the successful performance of work. Pedagogical professionalism is a characteristic of a variety of interrelated components that reflect a specific educational system that meets the social order of society
Keywords: professionalism; pedagogical activity; teacher; component